The Relationship between Social Economic Levels and Anemia Events in Pregnant Women in Glugur Darat Health Center - Noviyanti, Berliana; Simanjuntak, Harry C; Hutasoit, Eka Samuel P; Silitonga, Hendrika A; Julianto, Endy (Journal of Maternal and Child Health, 2019)
Background: Anemia is a condition where the hemoglobin level in the blood was lower than normal. Anemia diagnosed when the hemoglobin level was <11 gr / dl in the first and third trimesters or <10.5 gr% in the second trimester in pregnant women. WHO stated in 2010 that 40% of the causes of maternal mortality in developing countries were associated with ane